2015
DOI: 10.2903/j.efsa.2015.4178
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on an application (Reference EFSA‐GMO‐NL‐2011‐100) for the placing on the market of the herbicide‐tolerant, increased oleic acid genetically modified soybean MON 87705 × MON 89788 for food and feed uses, import and processing under Regulation (EC) No 1829/2003 from Monsanto

Abstract: The EFSA GMO Panel previously assessed the two single events combined to produce soybean MON 87705 × MON 89788 and did not identify safety concerns. No new data on the single events affecting the previous conclusions were identified. No differences in composition requiring further assessment were observed between soybean MON 87705 × MON 89788 and its comparator, except for the intended trait i.e. an altered fatty acid profile. Nutritional assessment on soybean MON 87705 × MON 89788 oil and oil‐containing food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
(43 reference statements)
1
4
0
Order By: Relevance
“…The updated bioinformatic analyses confirm the previous conclusions on the likelihood of occurrence of horizontal gene transfer for soybean MON 89788 event (EFSA GMO Panel, 2015b). It was concluded that the unlikely, but theoretically possible, horizontal transfer of recombinant genes from soybean MON 89788 to bacteria did not raise any environmental safety concern.…”
Section: Evaluation Of the Updated Bioinformatic Datasupporting
confidence: 79%
“…The updated bioinformatic analyses confirm the previous conclusions on the likelihood of occurrence of horizontal gene transfer for soybean MON 89788 event (EFSA GMO Panel, 2015b). It was concluded that the unlikely, but theoretically possible, horizontal transfer of recombinant genes from soybean MON 89788 to bacteria did not raise any environmental safety concern.…”
Section: Evaluation Of the Updated Bioinformatic Datasupporting
confidence: 79%
“…Effects of temperature and pH on CP4 EPSPS and Cry3Bb1 proteins have been previously evaluated by the EFSA GMO Panel (EFSA GMO Panel, 2009, 2015b, 2015c, 2017a. No new studies were provided in the context of this application.…”
Section: Influence Of Temperature and Ph On Newly Expressed Proteinsmentioning
confidence: 99%
“…The EFSA guidance seems to adopt this approach. Nonetheless, the traditional industry practice and recent regulatory opinions indicate that the safety of a GM crop is evaluated at each specific endpoint (literature listed in Table 1; EFSA 2015 a , b , c , 2016). This supports grouping the two comparisons at a given endpoint into a family, i.e.…”
Section: Methodsmentioning
confidence: 99%